Ability of three yellow pigment producing fungi to colour wood under controlled conditions. (May 2014) - Robinson, S. C.; Tudor, D.; Zhang, W. R.; Ng, S.; Cooper, P. A.
<x content-type="archive" xml:space="preserve">Abstract</x> Inonotus hispidus, Scytalidium ganodermophthorum and two strains of Scytalidium lignicola were tested for their ability to produce yellow extracellular pigment on media plates, sterile wood blocks and non-sterile logs to determine their suitability for use as spalting fungi. All three fungi produced a penetrating yellow pigment in the non-sterile logs after 12 weeks of incubation; however, results from the sterile block tests indicated that the incubation time necessary for I. hispidus to produce sufficient yellow pigment may be as low as 4 weeks of incubation. An incubation period of 4 weeks is the shortest recorded for controlled spalting and will allow for the currently utilised production time for yellow spalted wood of 12 weeks to be substantially decreased using an isolate of I. hispidus as the inoculum.